C677T polymorphism of the MTHFR gene and variant hemoglobins: a study in newborns from Salvador, Bahia, Brazil - Fábio David Couto; Elisângela Vitória Adorno; Joelma Figueiredo Menezes; José Pereira Moura Neto; Marco Antônio Vasconcelos Rêgo; Mitermayer Galvão dos Reis; Marilda Souza Gonçalves
The C677T polymorphism in the methylenetetrahydrofolate reductase gene (MTHFR) is associated with an increase in total homocysteine serum levels (tHcy), described as a risk factor for cardiovascular disease. Eight hundred forty-three neonates from two different maternity hospitals, one public and another private, in Salvador, Bahia, Brazil were screened for this polymorphism by PCR and RFLP. The T-allele frequency in the total sample was 0.23, and the prevalence rates of heterozygous and homozygous carriers were 36.2% and 5.3%, respectively. The T-allele frequency differed and the T/T genotype was more prevalent at the private maternity hospital. The hemoglobin (Hb) profile was investigated by HPLC in 763 newborns. The frequency of variant Hb was higher at the public than at the private maternity hospital. The association of the C677T polymorphism and the Hb profile was investigated in 683 newborns, showing a relatively high frequency of variant Hbs and the T allele. These data could provide an important basis for further studies focusing on potential risks of vaso-occlusive events in these individuals.